Exploring stress coping strategies of frontline emergency health workers dealing Covid-19 in Pakistan: A qualitative inquiry - Munawar, Khadeeja; Choudhry, Fahad Riaz (American journal of infection control, 2021)
•Studies on the psychological impact and mental health of people during the COVID-19 are limited.•Hence, this study investigated how emergency healthcare workers (HCWs) dealt with COVID-19 pandemic, their stress coping strategies or protective factors against stress eventually contributing to their mental health, and challenges they faced while dealing with COVID-19 patients.•Emergency HCWs practiced and recommended various coping strategies to deal with stress and anxiety emerging from COVID-19 pandemic.•Role of media in exacerbating mental health issues as well as limited self-disclosure to prevent distress among significant others was highlighted.•Religious coping, resilience and managing emotions maintained mental health of participants. [Display omitted] The COVID-19 outbreak has gravely impacted the physical and psychological health of people. As the outbreak is ongoing, it is crucial to equip the emergency healthcare workers (HCWs) to be medically and psychologically prepared. To examine the psychological impact of COVID-19 on emergency HCWs and to understand how they are dealing with COVID-19 pandemic, their stress coping strategies or protective factors, and challenges while dealing with COVID-19 patients. Using a framework thematic analysis approach, 15 frontline emergency HCWs directly dealing with COVID-19 patients from April 2, 2020 to April 25, 2020. The semi-structured interviews were conducted face-to-face or by telephone. Data were analyzed using thematic analysis. Findings highlighted first major theme of stress coping, including, limiting media exposure, limited sharing of Covid-19 duty details, religious coping, just another emergency approach, altruism, and second major theme of Challenges includes, psychological response and noncompliance of public/denial by religious scholar. Participants practiced and recommended various coping strategies to deal with stress and anxiety emerging from COVID-19 pandemic. Media was reported to be a principal source of raising stress and anxiety among the public. Religious coping as well as their passion to serve humanity and country were the commonly employed coping strategies.